PEMBERDAYAAN GURU MELALUI STRATEGI MANAJEMEN KELAS UNTUK MENINGKATKAN KREATIVITAS SISWA DI MADRASAH IBTIDAIYAH AL ISLAM SUTOPATI - Slamet, Tri; Athi, Fina Umu Rif; Hasyim HS, Ahmad Fuad Hasyim HS; Shiddiqy, Fikri Hakim Ash (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
The success of learning in madrasahs heavily depends on effective classroom management. At Madrasah Ibtidaiyah Al Islam Sutopati 3, challenges were identified, including limited learning media, lack of teaching method variety, and classroom layouts that did not fully support active student participation. This community service program employed the Asset-Based Community Development (ABCD) method to optimize the potential of teachers and school facilities. The program involved 5 teachers and 25 students from grades IV and V through structured classroom management assistance. Evaluation results showed a 40% increase in classroom management effectiveness, measured through student participation observation sheets. Furthermore, teacher creativity in designing simple learning media improved, creating a more interactive learning atmosphere. Asset-based classroom management optimization is proven to be a crucial strategy in building a creative learning ecosystem at the Madrasah Ibtidaiyah level.